2019
DOI: 10.1029/2019gl081932
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Circulation Patterns Associated With Wildfires in the Monsoon Regions of China

Abstract: Major atmospheric circulation patterns for wildfires have been identified in regions with boreal, Mediterranean, and semiarid climates. This study investigates such patterns in the monsoon regions of China, where the climate is controlled by multiple atmospheric systems and wildfires have large spatial variability. We identified three patterns. The first pattern was characterized by a high‐pressure ridge in northeast China and contributed to wildfires by creating warmer and drier conditions. The second, meridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…We classified the gridded monthly WFAC network into ten distinct fire regions using rotated principal component analysis (RPCA, see “Methods” and Supplemental material for details) that resemble previous spatial classifications of climate 33 and wildfire in China 24 27 . The WFAC fire chronologies for the whole country (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified the gridded monthly WFAC network into ten distinct fire regions using rotated principal component analysis (RPCA, see “Methods” and Supplemental material for details) that resemble previous spatial classifications of climate 33 and wildfire in China 24 27 . The WFAC fire chronologies for the whole country (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fire patterns in China and their linkages with climate 24 29 have mostly been studied based on provincial field survey data at coarse resolution (on average ~300,000 km 2 ) 26 , 29 . Such studies have revealed broad-scale fire responses to temperature, precipitation, and wind variability, as well as oceanic and atmospheric modes, such as ENSO 24 29 . However, the climatic influences on fire activity are not well-quantified at the local scale.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the specific geographical location, topography, climate, and distribution of forest resources lead to the uniqueness of forest and grassland fires in Southwest China, which are characterized by a low fire intensity but high frequency. Forest and grassland fires in Southwest China mainly occur from November to May of the next year [26,27]. Statistical research shows that the three months with the highest number of fires are February to April [22,27].…”
Section: Study Areamentioning
confidence: 99%
“…South China is located in the subtropical monsoon climate zone, where there are low mountains and hills [1,2]. South China experiences the most plentiful rainfall in China, influenced by subtropical monsoons.…”
Section: Introductionmentioning
confidence: 99%